Experimental behaviour of innovative thermal spray coating materials for FREEDAM joints. (15th April 2017) - Ferrante Cavallaro, G.; Francavilla, A.; Latour, M.; Piluso, V.; Rizzano, G.
Abstract: This paper presents the results of an experimental activity performed within the FREEDAM project, which is a project granted by the European Community devoted to the development of a new design strategy, for structures in seismic zone, based on the application of friction dampers in connections. In this work the attention is focused on the selection of materials to be employed as friction pads in FREEDAM joints, providing alternative solutions based on the application by means of thermal spray techniques of carbides and of metallic or intermetallic materials on steel plates. To date, twelve tests on eight different coating materials combined with stainless steel plates have been realized. The tests performed until now, which are mainly devoted to evaluate the behaviour of the friction interfaces in terms of static and kinetic friction coefficient and in terms of degradation, are inspired to the sliding test proposed by EN1090-2 adopting the loading protocol suggested by the EN12159 for the qualification of seismic devices. The initial value of the friction coefficient and its evolution during the tests, have been determined for the different materials by monitoring the values of the forces of the bolts used to apply the pre-load to the friction interface and the value of the sliding force. The obtained results are presented both in terms of force-displacement curves and in terms of friction coefficient, providing a comparison between the performances of the analysed interfaces in terms of energy dissipation supply.